2002
DOI: 10.1063/1.1454202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of grain boundary trap states in polycrystalline–silicon thin-film transistors by mobility and capacitance measurements

Abstract: A method for evaluating localized grain boundary (GB) trap states in polycrystalline–silicon thin-film transistors (poly-Si TFTs) is proposed. Field effects in poly-Si TFTs are analyzed by decomposition of the two-dimensional Poisson’s equation. This analysis gives the theoretical basis for evaluating the localized GB trap state density. The trap states are evaluated with the GB barrier potential given by the activation energy of the effective mobility and with the surface potential calculated from the capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…[20][21][22] or as Gaussian terms used in refs. [26][27][28]. We chose to use Gaussian terms because the studies dealing with SPC films suggest a peak in trap states near the mid gap and we are considering SPC films in this work.…”
Section: Trap State Distribution Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] or as Gaussian terms used in refs. [26][27][28]. We chose to use Gaussian terms because the studies dealing with SPC films suggest a peak in trap states near the mid gap and we are considering SPC films in this work.…”
Section: Trap State Distribution Modelmentioning
confidence: 99%
“…These have consisted of single energy level models, 17,18) models with single 19) or double [20][21][22] exponential tail states, Gaussian shaped distributions 1,23,24) or both. 25,26) It has been suggested that while tail states dominate the above-threshold behavior, mid-gap states primarily effect the subthreshold behaviour. 19,20) Although in this study we are only concerned with the above-threshold region, to ensure a realistic model we choose to include both mid-gap and tail states.…”
Section: Trap State Distribution Modelmentioning
confidence: 99%
“…Unlike Ikeda's results, [11][12][13] which consider the tunneling effect of the additional potential barrier as a fixed coefficient, the relation between M and D varies with v d .…”
Section: (D) In the Inversion Regionmentioning
confidence: 55%
“…2. The energy profile of N it in the poly-Si GB can be affected by various post-treatment methods, such as oxygen plasma, H 2 O vapor annealing, and hydrogen annealing [21], [22]. We use a similar peak value and distribution shape of the N it as in the previous studies without any treatments [23].…”
Section: Device Geometry and Simulation Methodologymentioning
confidence: 96%